Integrated Value Engineering with QFD and DFA as Product Design and Development Techniques: Literature Review - Handa Rivaldi Husal; Rosnani Ginting; Anizar Anizar (TALENTA Publisher, 2024)
Value engineering is an organized, rigorous strategy that assesses the performance, noise, quality, safety, and compatibility of systems, outfits, installations, services, and inventories to deliver necessary functionalities at the lowest life cycle cost. Eliminating unnecessary expenses from design, testing, production, operations, procedures, accounting, conservation, and other areas is the best course of action. The purpose of the paper's initial investigation was to list the drawbacks of value engineering in product creation. These transgressions highlight the necessity for alternative methods when implementing value engineering techniques. To address critical inverse issues throughout the process, from the stage of product demand analysis to product design, product, and operation, value engineering is combined with various engineering methods. The results demonstrate that there are distinct paths in which the benefit of integration engineering using QFD or DFA may be used. Even so, this integration is providing a better option for the planning of products or services through a process that not only means providing a better value for client satisfaction but also lowers expenses, shortening development times, and reducing the need for rework conditions—all without compromising performance, reducing anxiety, or lowering the quality of the final product.